2018
DOI: 10.1002/adsc.201701362
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalenediimide – A Unique Motif in Macrocyclic and Interlocked Supramolecular Structures

Abstract: This review presents as urvey through macrocyclic andi nterlocked structures containing 1,4,5,8-naphthalendiimide residues from the synthetic point of view and also illustrates the structural particularities that dictate their main applications in supramolecular, biological and materials chemistry. Thep aper is organised as ac omprehensived escription of macrocycles,c yclophanes,c atenanes,r otaxanes and metallamacrocyclesa long with other types of supramolecular interlockeda rchitectures.F or each category,w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 180 publications
(164 reference statements)
0
8
0
Order By: Relevance
“…In this regard, it provided an early practical tool for the synthesis of catenanes in satisfactory yields and served to further the likelihood of constructing higher-order entangled molecules. Since the beginning of the millennium, the blossoming of supramolecular-coordination-driven self-assembly involving various noncovalent interactions has been the basis for assembly of a variety of attractive interpenetrated structures, such as molecular links, rotaxanes, knots, and others. In addition, interlocked molecules with robust covalent skeletons have also been obtained directly through the entwining and threading of organic strands via hydrogen bonding, stacking interactions, anion coordination, or a combination of these noncovalent interactions. Furthermore, natural interlocked species have been found in biological systems, , such as knotted polynucleotide chains and protein architectures. A number of excellent reviews provide further reading and insights into specific aspects of known examples of interlocked architectures. …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it provided an early practical tool for the synthesis of catenanes in satisfactory yields and served to further the likelihood of constructing higher-order entangled molecules. Since the beginning of the millennium, the blossoming of supramolecular-coordination-driven self-assembly involving various noncovalent interactions has been the basis for assembly of a variety of attractive interpenetrated structures, such as molecular links, rotaxanes, knots, and others. In addition, interlocked molecules with robust covalent skeletons have also been obtained directly through the entwining and threading of organic strands via hydrogen bonding, stacking interactions, anion coordination, or a combination of these noncovalent interactions. Furthermore, natural interlocked species have been found in biological systems, , such as knotted polynucleotide chains and protein architectures. A number of excellent reviews provide further reading and insights into specific aspects of known examples of interlocked architectures. …”
Section: Introductionmentioning
confidence: 99%
“…The catalytic cycle of the mononuclear WOC [(cy)­Ru II bpy­(H 2 O)] 2+ has been systematically examined by means of a combination of theoretical and experimental techniques and consists of four proton-coupled electron transfer (PCET) steps. The free energy change of this WOC for each catalytic step from the initial intermediate I 1 to the final intermediate I 0 is reported in Table S1 and Figure S1 in the Supporting Information (SI) . The NDI chromophore family has shown good optical performance in photovoltaics, artificial photosystems, and all-polymer solar cells and potential in achieving photoinduced long-distance charge separation and reducing charge recombination. In a recent computational work, it has been shown that the NDI dye with diethoxy functional groups considered in this work performs fast electron injection in the TiO 2 semiconductor conduction band on a ps time scale . Furthermore, a very low activation barrier was estimated for the first water oxidation catalytic step upon photooxidation of the molecular photosensitizer (NDI +• ) covalently bound to the Ru-based WOC .…”
Section: Introductionmentioning
confidence: 99%
“…A second goal was to add crown ethers, that can be reversibly reduced from the neutral to the dianionic state, as these crown ethers become negatively charged upon electrochemical switching and thus are expected to cause a Coulomb attraction between the ammonium axle and the crown ether. The NDI moiety, which is readily applied in various redox-active MIMs, was selected because of its high stability and synthetic accessibility [ 42 ].…”
Section: Resultsmentioning
confidence: 99%